Unravelling the role of filler surface wettability in long-term mechanical and dielectric properties of epoxy resin composites under hygrothermal aging - Deng, Yuheng (2025)
Epoxy resin (EP) incorporating inorganic fillers has garnered significant attention in the electrical and electronic industries due to its enhanced dielectric and mechanical properties, but its long-term performance under harsh conditions remains a critical concern. This study investigates the effects of filler surface wettability on the durability of EP-SiO2 composites. Micro-sized SiO2 with hydrophilic (HP) and hydrophobic (HB) surfaces are prepared via surface treatment, before they are incorporated into epoxy resin and subjected to hygrothermal aging at 95 °C and 95 % relative humidity for up to 1200 h. Comprehensive characterizations of wettability, microstructure, mechanical properties, and dielectric performance are conducted. Results show that the composite with hydrophilic fillers, HP-SiO2-EP, exhibits superior dispersion and interfacial adhesion compared to its hydrophobic counterpart, HB-SiO2-EP. Consequently, HP-SiO2-EP demonstrates higher initial tensile strength, Young's modulus, and dielectric breakdown strength. Finite element simulations reveal the breakdown mechanism, highlighting that the hydrophobic SiO2 filler with interfacial defects results in earlier mechanical and dielectric failure. Furthermore, HP-SiO2-EP shows better resistance to hygrothermal aging compared to HB-SiO2-EP, with smaller increases in dielectric constant (+13 % vs. +28 %) and dielectric loss (+234 % vs. +311 %), as well as lower decrease in volume resistivity (-89 % vs. -93 %). This study provides valuable insights into the relationship between filler surface wettability and long-term composite performance, contributing to the design of more reliable materials for advanced dielectric applications.